CHIA PROTEIN CONCENTRATE (SALVIA HISPANICA L.) ANTI-INFLAMMATORY AND ANTIOXIDANT ACTIVITY - M, CÃrdenas; C, Carpio; J, Welbaum; E, Vilcacundo; W, Carrillo (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to evaluate the antioxidant and anti-inflammatory activity of chia proteins concentrates in in vitro conditions. Methods: Chia seeds (Salvia hispanica) were utilized to obtain chia protein concentrate at different pH 2.0, pH 3.0, pH 4.0, pH 5.0, and pH 6.0 using the isoelectric precipitation method and to evaluate the in vitro anti-inflammatory and in vitro inhibition of peroxidation lipid of chia protein concentrates. Results: The best treatment to obtain chia protein concentrate was at pH 3.0 with a value of 25.53% yield using water as solvent and 38.13% yield using NaCl 1M as solvent. The higher protein content was found in the chia protein concentrate at pH 4.0 with values of 91.18% and 57.87% of protein content. All chia protein concentrates presented high in vitro anti-inflammatory activity and inhibition peroxidation lipid. Chia protein concentrate at pH 3.0 (100–100 μg/ml) presented anti-inflammatory activity with values ranging from 56.32% to 103.00% in a form dependent doses. Chia protein concentrate at pH 6.0 presented a value range of 92.80–95.98% of inhibition of peroxidation lipid. Conclusion: This study suggests that chia protein concentrates possess potent antioxidant and anti-inflammatory activities in in vitro conditions.